Incurred sample reanalysis comparison of dried blood spots and plasma samples on the measurement of lopinavir in clinical samples. (February 2012) - Meesters, Roland JW; Hooff, Gero P; Gruters, Rob; van Kampen, Jeroen JA; Luider, Theo M
Background: Undoubtedly, incurred sample reanalysis (ISR) will become an integral part of regulated bioanalysis of dried blood spot (DBS) samples. In this article, we report results from an ISR study on DBS specimen and their corresponding plasma samples. Incurred samples were reanalyzed on their concentration of the antiretroviral drug lopinavir (LPV).Results: Bland–Altman comparison plots showed a high degree of agreement between the measurements; 94.7% of observed LPV concentrations were within bias ±2 SD. Moreover, 73.7% of obtained LPV concentrations from DBS ISR were in good compliance with general acceptance criteria (4-6-20 rule) on ISR testing, while plasma ISR failed on these acceptance criteria due to the low compliance of 10.5%.Conclusion: It was demonstrated that plasma ISR testing failed on acceptance criteria while corresponding incurred DBS specimens passed. Furthermore, the current article demonstrates that the stability of the antiretroviral drug LPV was significantly different in both biological matrices.